CNS tumors with PLAGL1-fusion: beyond ZFTA and YAP1 in the genetic spectrum of supratentorial ependymomas - Tauziède-Espariat, Arnault; Nicaise, Yvan; Sievers, Philipp; Sahm, Felix; Deimling, Andreas von; Guillemot, Delphine; Pierron, Gaëlle; Duchesne, Mathilde; Edjlali, Myriam; Dangouloff-Ros, Volodia; Boddaert, Nathalie; Roux, Alexandre; et al. (Acta Neuropathologica Communications, 2024)
A novel methylation class, “neuroepithelial tumor, with PLAGL1 fusion” (NET-PLAGL1), has recently been described, based on epigenetic features, as a supratentorial pediatric brain tumor with recurrent histopathological features suggesting an ependymal differentiation. Because of the recent identification of this neoplastic entity, few histopathological, radiological and clinical data are available. Herein, we present a detailed series of nine cases of PLAGL1-fused supratentorial tumors, reclassified from a series of supratentorial ependymomas, non-ZFTA/non-YAP1 fusion-positive and subependymomas of the young. This study included extensive clinical, radiological, histopathological, ultrastructural, immunohistochemical, genetic and epigenetic (DNA methylation profiling) data for characterization. An important aim of this work was to evaluate the sensitivity and specificity of a novel fluorescent in situ hybridization (FISH) targeting the PLAGL1 gene. Using histopathology, immunohistochemistry and electron microscopy, we confirmed the ependymal differentiation of this new neoplastic entity. Indeed, the cases histopathologically presented as “mixed subependymomas-ependymomas” with well-circumscribed tumors exhibiting a diffuse immunoreactivity for GFAP, without expression of Olig2 or SOX10. Ultrastructurally, they also harbored features reminiscent of ependymal differentiation, such as cilia. Different gene partners were fused with PLAGL1: FOXO1, EWSR1 and for the first time MAML2. The PLAGL1 FISH presented a 100% sensitivity and specificity according to RNA sequencing and DNA methylation profiling results. This cohort of supratentorial PLAGL1-fused tumors highlights: 1/ the ependymal cell origin of this new neoplastic entity; 2/ benefit of looking for a PLAGL1 fusion in supratentorial cases of non-ZFTA/non-YAP1 ependymomas; and 3/ the usefulness of PLAGL1 FISH.